PENGARUH INFORMASI NILAI GIZI DAN KEMASAN TERHADAP PEMBELIAN TELUR OMEGA-3 - Syahendri, Arsyad; Adinugroho, Mochammad Farrel; Oktavinia, Mona Salsa; Jenie, Razief Akbar Syah; Simatupang, Parhimpunan (JURNAL LENTERA BISNIS, 2026)
Indonesia faces a double burden of malnutrition, where stunting and obesity are major health issues. Omega-3 eggs emerge as a functional food solution rich in nutrients to support child development. This study aims to analyze the effect of Nutritional Information, Packaging Safety, and Consumer Lifestyle on Purchasing Decisions of omega-3 eggs among housewives in Jakarta. This quantitative study used a survey method with purposive sampling technique involving 208 housewife respondents residing in DKI Jakarta. Data were analyzed using Partial Least Squares (PLS) based Structural Equation Modeling (SEM) with SmartPLS software. The results showed that Nutritional Information (X1) and Consumer Lifestyle (X3) had a positive and significant effect on Purchasing Decisions (Y), with Lifestyle being the dominant factor. However, Packaging Safety (X2) did not have a significant effect on purchasing decisions. These findings indicate that consumers prioritize health benefits and product functional value over mere physical packaging aspects. Producers are advised to focus on nutritional education and target the health-conscious consumer segment.